2019
DOI: 10.1182/blood-2018-10-878082
|View full text |Cite
|
Sign up to set email alerts
|

CXCL1 regulates neutrophil homeostasis in pneumonia-derived sepsis caused by Streptococcus pneumoniae serotype 3

Abstract: Neutrophil migration to the site of bacterial infection is a critical step in host defense. Exclusively produced in the bone marrow, neutrophil release into the blood is tightly controlled. Although the chemokine CXCL1 induces neutrophil influx during bacterial infections, its role in regulating neutrophil recruitment, granulopoiesis, and neutrophil mobilization in response to lung infection-induced sepsis is unclear. Here, we used a murine model of intrapulmonary Streptococcus pneumoniae infection to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 49 publications
3
73
0
Order By: Relevance
“…Sepsis is caused by an overshooting answer of the immune system on the infection, resulting in injuring its own organs. This acute pro-inflammatory response of the body is mainly driven by polymorphonuclear neutrophils (PMNs) as the first cells of the immune system to be recruited to the side of inflammation (7,8). Accordingly, PMNs are considered as a prognostic marker for mortality in terms of sepsis (9) as they migrate from the circulatory system into the inflamed tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis is caused by an overshooting answer of the immune system on the infection, resulting in injuring its own organs. This acute pro-inflammatory response of the body is mainly driven by polymorphonuclear neutrophils (PMNs) as the first cells of the immune system to be recruited to the side of inflammation (7,8). Accordingly, PMNs are considered as a prognostic marker for mortality in terms of sepsis (9) as they migrate from the circulatory system into the inflamed tissue.…”
Section: Introductionmentioning
confidence: 99%
“…In OF-induced equine laminitis, increased gene expression of CXCL-1 and MCP-2 and the migration of neutrophils and mononuclear cells into lamellae are observed (20). A recent study reported that CXCL-1 could induce neutrophils to infiltrate the sites of bacterial infection and was involved in the granulopoiesis and mobilization of neutrophils in sepsis (56). Furthermore, MCP-2 is another important chemokine in inflammation and immunomodulation, which could activate mononuclear cells and direct them into target tissues (57).…”
Section: Discussionmentioning
confidence: 99%
“…Our current study elucidates a regulatory mechanism mediated by the miR-127/A20/STAT3 axis, which plays a key role in modulating macrophage anti-bacterial responses. However, as STAT3-driven anti-microbial signaling is also triggered by other immune cell subsets such as innate lymphoid cells and gd T cells (Baral et al, 2018;Xiong et al, 2016;Paudel et al, 2019), we currently cannot exclude the effect of miR-127 on these cells' response to bacterial infection, the topic of which is currently under investigation in our lab.…”
Section: Limitations Of the Studymentioning
confidence: 99%